Augmented Reality Application as Interactive Learning Media Traditional Weapons using Unity AR - Nafiz, Mohammad Fadhil Hardiansyah; Hamzah, Muhammad Luthfi; Saputra, Eki; Fronita, Mona (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Technological advancements have widely permeated Indonesian society, particularly in education. The challenges of globalization and modernization are expected to pose new challenges for the education sector in creating interactive learning media to support the interest and willingness to learn among the younger generation, who are already dominated by current technology. Therefore, innovative and engaging learning approaches are necessary for students to actively participate in the teaching and learning process. The use of Augmented Reality (AR) is said to foster creativity, partial imagination, and help control learning according to their preferred learning styles, allowing teachers to create learning environments tailored to students' cognitive styles. This research directly integrates augmented reality applications as a cultural arts learning media, where students are assisted in learning innovatively and can actively interact with traditional weapons in Indonesia virtually. This aids teachers in providing instruction on weapons without the need to fear the physical dangers of weapon use. The agile method is utilized to ensure that changes are embraced, and evolving requirements can be readily accommodated, providing clients with a guarantee of adaptability. The implementation of the augmented reality application has received a very positive response with a score of 85.75%, indicating that it is well-received by MTsN Gema students.